Optimizing pain control through the use of implantable pumps - Boris Todoroff (Dove Medical Press, 2008)
Wilfried Ilias1, Boris Todoroff21Dept Anesthesiology, Intensive Care Medicine and Pain Therapy, Academic Teaching Hospital St. John of God, Vienna, Austria; 2Dept. Plastic and Reconstructive Surgery, Hospital of St. Vincent, Vienna, AustriaAbstract: Intrathecal therapy represents an effective and well established treatment of nonmalignant as well as malignant pain. Devices available include mechanical constant flow pumps as well as electronic variable flow pumps with patient-controlled bolus release. The latter provide faster dose finding, individual pain control, and good acceptance by patients. New technologies such as membrane pumps and rechargeable devices are expected to be developed to clinical perfection. The available drugs for intrathecal therapy are listed according to the polyanalgesic consensus on intrathecal therapy. The integration of remote patient-controlled analgesia into electronic implantable devices, and the peptide analgesic ziconotide, have significantly improved intrathecal therapy. Complications include infections, catheter ruptures or disconnections, catheter granulomas, and technical dysfunctions. Further possibilities for optimizing intrathecal therapy include development of new drugs, drug side effects, catheter and pump technologies, and surgical techniques.Keywords: intrathecal therapy, implantable pumps, morphine pumps, intrathecal drugs, intrathecal catheters, intrathecal pain control